2014
DOI: 10.3109/21678421.2014.893361
|View full text |Cite
|
Sign up to set email alerts
|

RandomForest4Life: A Random Forest for predicting ALS disease progression

Abstract: We describe a method for predicting disease progression in amyotrophic lateral sclerosis (ALS) patients. The method was developed as a submission to the DREAM Phil Bowen ALS Prediction Prize4Life Challenge of summer 2012. Based on repeated patient examinations over a three month period, we used a random forest algorithm to predict future disease progression. The procedure was set up and internally evaluated using data from 1197 ALS patients. External validation by an expert jury was based on undisclosed inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 24 publications
(31 reference statements)
1
53
0
Order By: Relevance
“…Team 3 (ref. 15) won a third place prize of $10,000. As in previous installments of the DREAM challenges 16 , the aggregation of predictions across teams 1 and 2 further reduced the prediction error.…”
Section: Methods Performance and Assessmentmentioning
confidence: 99%
“…Team 3 (ref. 15) won a third place prize of $10,000. As in previous installments of the DREAM challenges 16 , the aggregation of predictions across teams 1 and 2 further reduced the prediction error.…”
Section: Methods Performance and Assessmentmentioning
confidence: 99%
“…The same conclusion can be drawn from the observation that diagnostic delay is a strong prognostic factor, since the implication is that the progression slope until diagnosis is similar to the slope after diagnosis. However, it has been noted in various studies that the ALSFrS-r progression rate can decrease, and sometimes even show a change in the positive direction between follow-up visits (33)(34)(35)(36)(37)(38). A study examining the relationship between spread and prognosis (10) showed that involvement of two regions within three months of onset -defined as the 'rapid-spread type' -was associated with a poor prognosis.…”
Section: Discussionmentioning
confidence: 98%
“…The effect of the dominant variable on the change of a patient's functional status, namely, the time between disease onset and treatment start, seems to be primarily prognostic according to the original MOB, whereas the predictive effect of calcium has been obscured by the prognostic effects and only becomes apparent with the application of the predMOB. However, the PRO‐ACT data base is a mixture of diverse trials and the membership of a patient to the respective study is not traceable . Hence, the meaningfulness and generalizability of the results are debatable.…”
Section: Discussionmentioning
confidence: 99%